Florence Welch em tradução: análise das traduções dos poemas monster e become a beacon para a língua portugesa - Kasmarek, Leonardo Rigon (2019)
The following research has the aim of developing an analysis from the translations of the poems Monster and Become a Beacon by Florence Welch inserted in the book Useless Magic to Portuguese done for me as a traslator/researcher. We analyse the final translations as product supported theoretically by polysystem theory by Itamar Even-Zohar (1970), Descriptive Translation Stuudies by Gideon Toury (1995), Technical Procedure of Translation by Lanzetti et. al. (2006), among others theorists. One of the aims of this research is to introduce Florence Welch into Brazilian literary polysystem, in order to introduce her literary work for Brazilian readers, as long as there is no academic works about the author in Brazilian’s research websites. Another objective of the present research is to analyze the translated texts and to verify verify which elements were maintained or tamed to Brazilian polysystem, observing which were the translator’s choices about rhythm, structure, etc. The research has shown that the poem’s translation had, most of time, a maintance inclination, keeping the translations similar to the source-language, except for some specific itens that were tamed to make sense to Brazilian polysystem readers.